Studies in marine diterpene chemistry - Van Wyk, Albert Wynand Wincke (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
This thesis comprises both a natural product investigation and a synthetic component. The natural product investigations are presented in Chapters Two and Three. In Chapter Two the isolation and spectroscopic identification of the new isocopalane diterpene 12S,13R,14Sisocopalan- 13-ol-12,14-diacetate (2.1) and two known 3-(14S)-isocopal-12-ene-15-oyl-1- acetyl-sn-glycerol (2.2) and 3-(14S)-isocopal-12-ene-15-oyl-2-acetyl-sn-glycerol (2.3) from a single, large, unidentified sub-Antarctic nudibranch, collected near Marion Island, approximately 2000 km south of Cape Town are described. Chapter Three discusses the isolation, spectroscopic structure elucidation and anti-oesophageal cancer activity (3.1-3.4 only) of two known labdane diterpenes 6Î²,7Î±-diacetoxylabda-8,13E-dien-15-ol (3.1) and 2Î±,6Î²,7Î±-triacetoxylabda-8,13E-dien-15-ol (3.2) and one new 6Î²,7Î±,15-triacetoxylabda 8,13E-diene (3.3), as well as new 3Î±,11-dihydroxy-9,11-seco-cholest-4,7-dien-6,9-dione (3.4) and cholest 7-en-3,5,7-triol (3.5) from the endemic pulmonate mollusc, Trimusculus costatus. The absolute configuration of 3.2, and hence 3.1 and 3.3 (from biogenetic arguments) was determined through X-ray diffraction of a single crystal of the camphanate ester of 3.2. The absolute configuration of the secondary hydroxyl at C-3 of 3.4 was established using the Modified Mosher's method. The synthetic component of the thesis commences in Chapter Four with the semi-synthesis of labdane diterpene nitriles 9Î±-cyano-15,16-epoxy-7Î²-hydroxylabda-13(16),14-dien-6-one (4.1), 9Î±-cyano-15,16-epoxy-7-hydroxylabda-7,13(16),14-trien-6-one (4.2) and 9Î±-cyano-15,16- epoxy-6Î²,7Î² dihydroxylabda-13(16),14-diene (4.3) from the terrestrial labdane diterpene, hispanolone (4.4). This work is an extension of previous synthetic studies directed towards the synthesis of T. costatus metabolites. Diterpenes 4.1-4.3 exhibited in planta activity against the economically important crop pathogens, Magnaporthea grisea and Puccinia recondita. Chapter Five describes the successful semi-synthesis of two isomeric marine molluscan labdane diterpene aldehyde metabolites, labd-13E-ene-8Î²-ol-15-al (5.1) and labd-13Z-ene- 8Î²-ol-15-al (5.2) from the commercially available, terrestrial plant derived, labdane diterpene manool (5.3). Diterpenes 5.1 and 5.2, originally isolated from the Mediterranean nudibranch,Pleurobranchaea meckelii and selected diterpenes arising from this synthesis were evaluated for their activity against an oesophageal cancer cell line (WHCO1). Chapter Six further develops the research discussed in Chapter Five, where ethyl 17-norabiet-13(15)-E-en-8Î²-ol- 16-oate (5.49) and ethyl 17-norabiet-13(15)-Z-en-8Î²-ol-16-oate (5.50) were first semisynthesized serendipitously. Based on their structural relationship to naturally occurring tricyclic diterpenes with anti-plasmodial activity, tricyclic diterpenes, 17-norpimaran-13Î±- ethoxy-8,16-olactone (6.6), 17-norisopimar-15-ene-8Î²,13Î²-diol (6.7), 17-norisopimarane- 8Î²,16-diol (6.8) and 17-norabiet-13(15)-ene-8Î²,16-diol (6.9) were semi-synthesized from the terrestrial labdane diterpene, 5.3, and critically evaluated for their antimalarial potential from parasite inhibition and haemolytic studies.
Keywords: Natural products; Diterpenes; Mollusks; Marine metabolites; Chemical oceanography